Targeting tumor-associated macrophages in non-small cell lung cancer: mechanisms, prognosis, and therapeutic opportunities - Hao, Dameng; Chen, Shengjie (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) remains the most prevalent and lethal form of lung cancer worldwide. Among the diverse components of the tumor microenvironment, tumor-associated macrophages (TAMs) are increasingly recognized as key regulators of NSCLC progression, metastasis, and treatment resistance. TAMs, particularly those polarized toward the M2-like phenotype, facilitate tumor growth through immunosuppression, angiogenesis, epithelial–mesenchymal transition, and extracellular matrix remodeling. They promote immune evasion via PD-L1, IL-10, and TGF-β signaling, and confer chemoresistance through activation of the IL-6/STAT3 and P2X7/STAT6 pathways. Moreover, high infiltration of M2-TAMs and their expression of immune checkpoint ligands have been associated with poor prognosis and, paradoxically, with improved response to PD-1/PD-L1 blockade in certain patients. Emerging therapeutic strategies aim to reprogram TAM phenotypes, inhibit their recruitment, or selectively suppress their immunosuppressive functions. However, challenges such as macrophage plasticity, lack of specific biomarkers, and potential systemic toxicity remain significant barriers. This review provides a comprehensive overview of the biological functions, mechanistic roles, and clinical implications of TAMs in NSCLC, highlighting both their value as prognostic indicators and their potential as therapeutic targets in the era of precision oncology.